2014
DOI: 10.1177/2158244014548847
|View full text |Cite
|
Sign up to set email alerts
|

A Program Review

Abstract: The purpose of this study was to discover the transformation preschool teacher candidates go through in their perceptions about teacher and teaching during their teacher education program. The participants of the study were 35 senior students enrolled in the preschool teacher education program at a university located in the Eastern Anatolian Region of Turkey. A qualitative survey instrument was conducted to examine the preservice teachers' perceptions. The data collected from the survey were analyzed by adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…Similar reasons for choosing the teaching profession have been documented in other studies (e.g. Aldemir and Kurt, 2014;Erkan et al, 2002;Manuel & Hughes, 2006). Kilinc, Watt, and Richardson (2012) investigated the rationale for becoming a teacher among Turkish preservice teachers of early childhood, primary, and secondary education, and their results indicated that altruistic social values were the most compelling reasons, followed by job security.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 68%
See 2 more Smart Citations
“…Similar reasons for choosing the teaching profession have been documented in other studies (e.g. Aldemir and Kurt, 2014;Erkan et al, 2002;Manuel & Hughes, 2006). Kilinc, Watt, and Richardson (2012) investigated the rationale for becoming a teacher among Turkish preservice teachers of early childhood, primary, and secondary education, and their results indicated that altruistic social values were the most compelling reasons, followed by job security.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 68%
“…Nevertheless, as participants in our study exemplified, an explanation for the increased percentage of men among the ranks of preservice ECE teachers could be an increased interest in the teaching profession due to the perceived convenience of state appointment and the promise of satisfactory wages. Teachers who graduate from faculties of education in Turkey are appointed by the state based on their PPSE scores, which guarantees them jobs upon graduation, as well as several benefits, including defined work hours, a stable salary, social security, and holidays, all of which make the teaching profession appealing to young Turks (Aldemir & Kurt, 2014;Yuce, Sahin, Kocer, & Kana, 2013;Yuksel, 2012).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final year of undergraduate education, preservice preschool teachers have practica/field experience as part of teacher training. Practica/field experience helps preservice teachers continue the transformation they experience throughout their program courses and gain crucial professional dispositions to work with young children and their families, teach in preschool classroom, and be an advocate for the profession (Aldemir & Kurt, 2014). Additionally, during practicum, preservice teachers are given the opportunity to experience and experiment their knowledge and skills in an authentic teaching and learning environment (Kennedy, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Preschool teacher education lasts four years in the Faculties of Education of these universities. When students graduate from Turkish preschool teacher education programs are granted their preschool/kindergarten teaching license, and are entitled to teach in public and private preschools and kindergarten classes (Aldemir & Kurt, 2014). In the final year of undergraduate education, preservice preschool teachers have practica/field experience as part of teacher training.…”
Section: Introductionmentioning
confidence: 99%